ACTUALIZATION OF ISLAMIC LAW IN THE SHARIA BUSINESS UNIT OF THE MAKASSAR BRANCH STATE SAVINGS BANK - M Husni Ingratubun (Sekolah Pascasarjana Universitas Swadaya Gunung Jati, 2023)
This research was conducted at the Sharia Business Unit of the State Savings Bank (BTN), Makassar Branch. The sample was selected purposively as many as 75 respondents. Data were analyzed descriptively using tables. The results of the study show that the low actualization of Islam in the Sharia Business Unit of the Makassar Branch of the State Savings Bank (BTN) has not gone well based on sharia principles. The position of employees in the Syariah Business Unit of the Makassar Branch of the State Savings Bank is experiencing a dilemma where in one position the Bank's employees are instructed to work based on Islamic Sharia in attracting customers while on the other hand they are given targets by management. State Savings Bank Sharia Business Unit (BTN), Makassar Branch. They will receive a negative valuation and will even receive sanctions from the management of the Makassar Branch Sharia Business Unit of the State Savings Bank (BTN) because they cannot reach the target.